Meningkatkan Kemampuan Mengenal Huruf Vokal Melalui Media Roda Putar Untuk Anak Usia 3-4 Tahun - Suci Windariyanti; Susi Herlinda; Herwina Herwina (PT. Riset Press International, 2026)
This study aims to determine the ability to recognize vowels of children aged 3-4 years at the Tunas Pertiwi Pejajaran Kindergarten, Bukit Kratai Village, Kampar Regency. The research used in this study is Classroom Action Research. The subjects of this study were children aged 3-4 years at the Tunas Pertiwi Pejajaran Kindergarten, totaling 15 children in one class. Based on the results of the application of research using rotating wheel media can improve the ability to recognize vowels. Based on the analysis of the data obtained, in the initial condition data in the pre-action before being given the action, the average percentage of the class in the initial condition was 29.17%, then in cycle I increased to 32.50%. Then in cycle II experienced a significant increase, reaching 76.25%. This study provides an alternative learning medium in the form of a spinning wheel that can be used to improve early childhood ability in recognizing vowel letters. In addition, it contributes to the development of innovative and engaging learning strategies for introducing vowel letters.